Low-carbon phase change energy storage UHPC and preparation method thereof

By introducing modified carbon fibers, polycarboxylic acid high-performance water reducing agents, composite coagulation agents and phase change aggregates into UHPC, combined with multi-dimensional crack control methods, the cracking risk caused by early shrinkage of UHPC is solved, and higher mechanical properties and better temperature control capabilities are achieved.

CN119683938APending Publication Date: 2025-03-25CHINA CONSTRUCTION SIXTH ENGINEERING DIVISION CO LTD +2
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411864662.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

UHPC has a high risk of cracking during early shrinkage, mainly due to its self-contraction and temperature shrinkage, which leads to the formation of structures throughout and deep cracks.

Method used

Low-carbon phase-change energy storage UHPC is adopted, and its composition includes modified carbon fiber, polycarboxylic acid high-performance water reducing agent, composite coagulation agent and phase-change aggregate. Through multi-dimensional crack control method, the shrinkage behavior of concrete is adjusted, and the heat storage and release ability of phase-change aggregate is used to adjust the indoor temperature.

Benefits of technology

It effectively controls the self-shrinkage and temperature shrinkage of UHPC, reduces the risk of early cracking, improves the mechanical properties and heat conduction efficiency of concrete, and enhances the temperature control ability of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683938A_ABST
    Figure CN119683938A_ABST
Patent Text Reader

Abstract

The invention relates to a low-carbon phase change energy storage UHPC (Ultra High Performance Concrete) and a preparation method thereof. The low-carbon phase change energy storage UHPC comprises the following components in parts by weight: 1400 parts of cement, 320-400 parts of fly ash, 200-280 parts of silica fume, 400-480 parts of water, 1200 parts of machine-made sand, 1700 parts of phase change aggregate, 2 parts of modified carbon fiber, 20 parts of a polycarboxylic acid high-performance water reducing agent, 2 parts of a composite thickening time control agent and 1 part of sodium polyacrylate. The preparation method comprises the following steps: weighing materials; preparing concrete 1: preparing a mixed solution 1; stirring the concrete 1; preparing concrete (2); preparing mixed liquid (2); stirring the concrete (2); and pouring concrete, vibrating and curing. According to the method, UHPC shrinkage control is carried out by adopting a multi-dimensional crack control method, and penetrating cracks and deep cracks are prevented from being generated in a concrete structure; the provided phase change energy storage UHPC has the heat storage and release capacity, the indoor temperature can be adjusted, and resource energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a low-carbon phase-change energy storage UHPC and a preparation method thereof. Background Art

[0002] Ultra-High Performance Concrete (UHPC) is a new type of concrete that has attracted widespread attention from scholars since its introduction and has been used in bridges, houses and other projects. UHPC mainly refers to the design principle of Densified with Small Particals (DSP), and further adopts fibers with large aspect ratio and high toughness, so that it takes into account the advantages of fiber concrete and DSP. While obtaining ultra-high strength, toughness and durability, it can also significantly reduce the cross-sectional size of components.

[0003] Although UHPC has a high density, its low water-binder ratio and high cementitious material dosage still cause significant shrinkage. At the same time, the early shrinkage of UHPC (1-7 days) develops rapidly, accounting for 62.3%-86.5% of the total shrinkage. Therefore, the risk of early cracking of UHPC is still very high.

[0004] Similar to ordinary and high-performance concrete, it is generally believed that the shrinkage of UHPC is mainly composed of drying shrinkage, autogenous shrinkage and temperature shrinkage. Drying shrinkage is caused by the evaporation of internal moisture from the matrix due to the low humidity of the external environment of cement-based materials, which can generally be controlled by reasonable maintenance processes. Ordinary concrete shrinkage is mainly drying shrinkage, while UHPC is mainly autogenous shrinkage, and its autogenous shrinkage accounts for 78.6%-90.0% of the total shrinkage. Autogenous shrinkage is the shrinkage phenomenon of macroscopic volume caused by chemical shrinkage produced by the hydration reaction of cementitious materials. On the one hand, autogenous shrinkage is the "self-drying" shrinkage caused by the hydration of cementitious materials in concrete consuming water in the capillary pores, causing the internal humidity to decrease; on the other hand, autogenous shrinkage is caused by chemical reactions and is also chemical shrinkage. In addition, since UHPC is in a plastic flow state when it is just poured, cement will generate a large amount of hydration heat during the hydration reaction and condensation process, causing the volume to expand freely. When the highest temperature is reached, the concrete is basically solidified, and then the concrete begins to cool down and shrink to produce cracks. In the contact area with the formwork, the shrinkage of the concrete is constrained by the formwork, resulting in greater tensile stress, and through cracks and deep cracks will appear; if there is a cold wave, the temperature difference between the inside and outside of the concrete will be relatively large, and the deformation will be constrained by the internal concrete, and surface cracks will appear in the concrete. Summary of the invention

[0005] The present invention aims to control the autogenous shrinkage and temperature shrinkage of UHPC, and provide a low-carbon phase change energy storage UHPC and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A low-carbon phase-change energy storage UHPC, whose components and weight proportions are: 1400 parts of cement, 320-400 parts of fly ash, 200-280 parts of silica fume, 400-480 parts of water, 1200 parts of machine-made sand, 1700 parts of phase-change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0008] The cement is P·Ⅱ52.5 silicate cement.

[0009] The average particle size of machine-made sand is 130μm, the maximum particle size is 250μm, and the gradation is continuous.

[0010] The particle size of phase change aggregate is 8-11mm, and the preparation method is as follows:

[0011] S1. Granite surface modification: Granite is calcined at high temperature for surface modification to produce fine pores and granular materials, thereby increasing the roughness of the aggregate substrate to provide attachment sites for phase change materials;

[0012] S2. Vacuum adsorption of phase change material: n-dodecane is used as phase change material (its phase change temperature is 25°C, and its phase change latent heat is 105 J / g). A beaker containing liquid phase change material and modified granite is placed in a glass kettle and a vacuum pump is started for 30-40 minutes. When the modified granite immersed in the liquid phase change material no longer emits bubbles, the pores in the modified granite are completely filled with the phase change material.

[0013] S3. Post-processing of phase change aggregate: stop vacuuming, slowly turn the air inlet valve to restore the pressure in the glass kettle to normal pressure, take out the modified granite that has absorbed the phase change material and put it into a refrigerator at 4°C, and carry out subsequent packaging work after the phase change material in the modified granite becomes solid. The cement slurry is modified with 30% by mass epoxy resin and evenly wrapped on the outer surface of the phase change granite. The wrapping thickness is controlled to be 0.5-1.0mm, and the modified cement slurry is solidified to obtain the phase change aggregate.

[0014] The modification method of modified carbon fiber is as follows:

[0015] P1. Preparation of carboxylated carbon fiber: Weigh 5 parts of carbon fiber, the carbon fiber used is T700-12K carbon fiber, the length is 10 mm, pour it into a beaker filled with a mixed solution of 98% concentrated sulfuric acid and 70% concentrated nitric acid in a volume ratio of 3:1, stir evenly, put it into a magnetic stirring rotor and coat it, move the beaker to a magnetic heating stirrer, stir it at 300 rad / min for 6 hours under the condition of heating in a water bath at 60°C, take out the beaker and let it stand to room temperature, then dilute the mixed solution in the beaker, filter it with a vacuum filter, wash the oxidized carbon fiber to neutrality, put it in a vacuum oven, and dry it at 65°C for 24 hours to obtain carboxylated carbon fiber;

[0016] P2. Preparation of multi-walled carbon nanotube dispersion: Weigh 1 portion of carbon nanotubes, pour into a beaker containing 50 ml of dimethylformamide, add TNDWIS aqueous dispersant dropwise at a mass ratio of 1:5, stir magnetically for 15 minutes and then coat, move the coated beaker into an ultrasonic cell crusher, and ultrasonicate at 30% power for 30 minutes to obtain a multi-walled carbon nanotube dispersion;

[0017] P3. Modification of carbon fiber grafted with multi-walled carbon nanotubes: Add the carboxylated carbon fiber obtained in step P1 to the beaker containing the multi-walled carbon nanotube dispersion obtained in P2, then add a few drops of concentrated sulfuric acid, transfer to a constant temperature magnetic stirrer, heat in a 60°C water bath at 50% power, and turn on the ultrasonic equipment and magnetic stirring equipment at the same time, so that the mixed liquid is stirred while being ultrasonically treated, and the stirring speed is 450 rad / min, and the stirring is carried out for 2 hours. After the stirring is completed, remove the beaker from the device and let it stand to room temperature, and then use a vacuum filter to wash the reaction product several times, and finally put it into a vacuum drying oven and dry it at 65°C for 24 hours to obtain modified carbon fiber.

[0018] The composite coagulant is prepared by compounding 0.2% sodium citrate and 1% sodium gluconate.

[0019] The above-mentioned method for preparing a low-carbon phase change energy storage UHPC has the following specific steps:

[0020] Y1. Weighing materials:

[0021] According to the test mix ratio, calculate the mixing amount of each material, accurately weigh the mass of each material and divide it into two equal parts according to mass to prepare concrete ① and concrete ②;

[0022] Y2. Concrete① configuration:

[0023] Y21, mixed solution ① configuration: add polycarboxylic acid high-performance water reducing agent and composite setting agent to 50% water and stir for 3 minutes to obtain aqueous solution α; add modified carbon fiber and sodium polyacrylate to the remaining 50% water and stir for 3 minutes to obtain aqueous solution β containing modified carbon fiber;

[0024] Y22. Concrete ① Mixing: Place cement, fly ash and silica fume in a dry mixer and mix for 2 minutes; stop the mixer and add machine-made sand and mix for 1 minute; stop the mixer and add the phase change aggregate with pre-wetted surface and mix for 1 minute; keep stirring and add aqueous solution α and mix for 1 minute; keep stirring and add aqueous solution β containing modified carbon fiber and mix for 3 minutes to make the mixture evenly stirred;

[0025] Y3. Concrete② configuration:

[0026] Y31, mixed solution ② configuration: the aqueous solution γ does not contain a composite coagulant, and the rest of the configuration method is the same as the aqueous solution α; the aqueous solution ξ containing modified carbon fiber is configured in the same way as the aqueous solution β containing modified carbon fiber;

[0027] Y32. Concrete② Mixing: Place cement, fly ash and silica fume in a dry mixer and mix for 2 minutes; stop the mixer and add machine-made sand and mix for 1 minute; stop the mixer and add the phase change aggregate with pre-wetted surface and mix for 1 minute; keep stirring and add the aqueous solution γ and mix for 1 minute; keep stirring and add the aqueous solution containing modified carbon fiber ξ and mix for 3 minutes to make the mixture evenly stirred;

[0028] Y4. Concrete pouring, vibration and maintenance:

[0029] Pour concrete ① and concrete ② into their respective "L" deformed cross-section concrete pouring devices, keep the concrete surface 1 / 3 away from the top surface of the pouring device, open the movable baffle at the pouring device outlet containing concrete ①, and allow concrete ① to flow outwards into the mold coated with a release agent under the action of gravity. Each time the pouring reaches 1 / 4 of the height, place the test mold on a vibrating table, and expel the internal bubbles by vibrating to achieve a dense effect, until pouring reaches 1 / 2 of the test mold height; open the movable baffle at the pouring device outlet containing concrete ②, and allow concrete ② to flow outwards into the mold under the action of gravity. Each time the pouring reaches 1 / 4 of the height, place the test mold on a vibrating table, and expel the internal bubbles by vibrating to achieve a dense effect; after the concrete pouring and vibration are completed, scrape the film flat, and remove the mold after curing under natural conditions for 24 hours. After the demolding is completed, perform standard curing on the test piece.

[0030] The "L"-shaped variable-section concrete pouring device includes a vertical pipe, a direction-changing curved pipe, a variable-section pipe, a pouring device and a movable partition; the vertical pipe and the direction-changing curved pipe form an L-shaped structure, the variable-section pipe is connected to the outlet end of the vertical curved pipe, the variable-section pipe is connected to the inlet of the pouring device, and the movable partition is arranged at the outlet end of the pouring device.

[0031] The beneficial effects of the present invention are as follows: the present invention adopts a multi-dimensional crack control method to control UHPC shrinkage, thereby preventing through cracks and deep cracks from occurring in concrete structures; the provided phase change energy storage UHPC has the ability to store and release heat, can regulate indoor temperature, and reduce resource and energy consumption; the fiber dispersion and fiber orientation are taken into consideration, while improving the mechanical properties of concrete, ensuring its heat conduction efficiency, and improving the temperature control capability of concrete components. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a flow chart of the preparation method of low-carbon phase change energy storage UHPC in the present invention;

[0033] Figure 2 It is a structural schematic diagram of an "L" shaped variable cross-section concrete pouring device;

[0034] In the figure: 1-vertical pipe; 2-direction bending pipe; 3-variable cross-section pipe; 4-casting device; 5-movable partition;

[0035] The following is a detailed description of the embodiments of the present invention with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described in more detail by way of example with reference to the accompanying drawings in the following paragraphs. The advantages and features of the present invention will become clearer according to the following description. It should be noted that the accompanying drawings are all in a very simplified form and are not in precise proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0039] Phase change energy storage concrete is a type of concrete that uses PCM as latent heat storage material, taking advantage of its high energy storage density, low volume expansion rate, and ability to maintain approximately isothermal properties during the absorption or release of heat. Phase change energy storage materials are used in concrete. Through the phase change process, concrete can have phase change temperature regulation functions while also having certain mechanical properties. It is one of the new hot spots in international green building materials research today.

[0040] Therefore, PCM can be used as a strategy to control the temperature cracks of UHPC concrete and to control the water loss and setting agent of UHPC to prepare a low-carbon phase change energy storage UHPC, which provides a new idea for early crack control of UHPC concrete and solves the common industry problems of traditional UHPC. At the same time, based on reasonable fiber modification, fiber dispersion and fiber orientation are considered to improve the absorption and release efficiency of heat of phase change energy storage UHPC, and promote the technological progress of the UHPC industry and its large-scale application process. Specific embodiment 1:

[0042] A low-carbon phase-change energy storage UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 400 parts of fly ash, 200 parts of silica fume, 400 parts of water, 1200 parts of machine-made sand, 1700 parts of phase-change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0043] The cement is P·Ⅱ52.5 silicate cement.

[0044] The average particle size of machine-made sand is 130μm, the maximum particle size is 250μm, and the gradation is continuous.

[0045] The particle size of phase change aggregate is 8-11mm, and its preparation method is as follows:

[0046] S1. Granite surface modification: Granite is calcined at high temperature for surface modification to produce fine pores and granular materials, thereby increasing the roughness of the aggregate substrate to provide attachment sites for phase change materials.

[0047] S2. Vacuum adsorption of phase change material: using n-dodecane as the phase change material (its phase change temperature is 25°C, and the phase change latent heat is 105 J / g), placing the beaker containing the liquid phase change material and modified granite in a glass kettle and starting the vacuum pump for 30-40 minutes. When the modified granite immersed in the liquid phase change material no longer emits a large number of bubbles, it can be considered that the pores in the modified granite are basically filled with the phase change material.

[0048] S3, post-processing of phase change aggregate: after stopping the vacuuming, slowly turn the air inlet valve to restore the pressure in the glass kettle to normal pressure, take out the modified granite that has absorbed the phase change material and put it into a 4°C refrigerator, and carry out subsequent packaging work after the phase change material in the modified granite becomes solid; the cement slurry is modified with 30% by mass epoxy resin and then evenly wrapped on the outer surface of the phase change granite, and the wrapping thickness is controlled to be 0.5-1.0mm, and the phase change aggregate is obtained after the modified cement slurry solidifies.

[0049] The carbon fiber is T700-12K carbon fiber with a length of 10 mm. The modification method is as follows:

[0050] P1. Preparation of carboxylated carbon fiber: Weigh 5 parts of carbon fiber and pour them into a beaker containing a solution of 98% concentrated sulfuric acid and 70% concentrated nitric acid in a volume ratio of 3:1. Stir evenly and place in a magnetic stirring rotor and coat. Move the beaker to a magnetic heating stirrer, stir at 300 rad / min for 6 hours in a water bath heated at 60°C, take out the beaker and let it stand at room temperature, dilute the mixed solution in the beaker, filter and wash the oxidized carbon fiber to neutrality using a vacuum filter, and place in a vacuum oven at 65°C to dry for 24 hours.

[0051] P2. Preparation of multi-walled carbon nanotube dispersion: Weigh 1 portion of carbon nanotubes and pour it into a beaker filled with 50 ml of dimethylformamide, add TNDWIS aqueous dispersant dropwise at a mass ratio of 1:5, and coat the mixture after magnetic stirring for 15 minutes. Move the coated beaker into an ultrasonic cell crusher and ultrasonically treat it at 30% power for 30 minutes to obtain a multi-walled carbon nanotube dispersion.

[0052] P3. Modification of carbon fiber grafted with multi-walled carbon nanotubes: Add the carboxylated carbon fiber obtained in step P1 to the beaker containing the multi-walled carbon nanotube dispersion obtained in P2, then add a few drops of concentrated sulfuric acid, transfer to a constant temperature magnetic stirrer, heat in a 60°C water bath at 50% power, and turn on the ultrasonic equipment and magnetic stirring equipment at the same time, so that the mixed solution is stirred while being ultrasonically treated, and the stirring speed is 450 rad / min, and the stirring is carried out for 2 hours; after the stirring is completed, remove the beaker from the device and let it stand to room temperature, then use a vacuum filter to wash the reaction product several times, and finally put it into a vacuum drying oven and dry it at 65°C for 24 hours to obtain modified carbon fiber.

[0053] The composite coagulant is prepared by compounding 0.2% sodium citrate and 1% sodium gluconate.

[0054] like Figure 1 As shown, the preparation method of the above-mentioned low-carbon phase change energy storage UHPC is as follows:

[0055] Y1. Weighing materials: Calculate the mixing amount of each material according to the test mix ratio, accurately weigh the mass of each material and divide it into two equal parts to prepare concrete ① and concrete ②.

[0056] Y2. Concrete① configuration:

[0057] Y21. Mixed liquid ① configuration: add polycarboxylic acid high-performance water reducer and composite setting agent into 50% water and stir for 3 minutes to obtain aqueous solution α; add modified carbon fiber and sodium polyacrylate into the remaining 50% water and stir for 3 minutes to obtain aqueous solution β containing modified carbon fiber.

[0058] Y22. Concrete ① Mixing: Place cement, fly ash and silica fume in a dry mixer and stir for 2 minutes; stop the machine, add machine-made sand and stir for 1 minute; stop the machine, add the phase change aggregate with pre-wetted surface and stir for 1 minute; keep stirring, add aqueous solution α and stir for 1 minute, keep stirring, add aqueous solution β containing modified carbon fiber and stir for 3 minutes to make the mixture uniform.

[0059] Y3. Concrete② configuration:

[0060] Y31. Mixed liquid ② configuration: There is no composite coagulant in the aqueous solution γ, and the rest of the configuration method is the same as that of the aqueous solution α; the aqueous solution ξ containing modified carbon fiber is configured in the same way as the aqueous solution β containing modified carbon fiber.

[0061] Y32. Concrete②Mixing: Place cement, fly ash and silica fume in a dry mixer and stir for 2 minutes; stop the machine, add machine-made sand and stir for 1 minute; stop the machine, add the phase change aggregate with pre-wetted surface and stir for 1 minute; keep stirring, add the aqueous solution γ and stir for 1 minute, keep stirring, add the aqueous solution containing modified carbon fiber ξ and stir for 3 minutes to make the mixture uniform.

[0062] Y4. Concrete pouring, vibration and curing: pour concrete ① and concrete ② into their respective "L" deformed cross-section concrete pouring devices, keep the concrete surface 1 / 3 away from the top surface of the pouring device, open the movable baffle 5 at the pouring device outlet containing concrete ①, so that concrete ① flows outwards into the mold coated with a release agent under the action of gravity, and each time the concrete is poured to 1 / 4 of the height, place the test mold on the vibration table, and vibrate to expel the internal bubbles to achieve a dense effect, until the concrete is poured to 1 / 2 of the test mold height; open the movable baffle 5 at the pouring device outlet containing concrete ②, so that concrete ② flows outwards into the mold under the action of gravity, and each time the concrete is poured to 1 / 4 of the height, place the test mold on the vibration table, and vibrate to expel the internal bubbles to achieve a dense effect; after the concrete pouring and vibration are completed, scrape the film flat, and remove the mold after curing under natural conditions for 24 hours. After the demolding is completed, perform standard curing on the test piece.

[0063] "L" deformation cross-section concrete pouring device Figure 2 As shown, it includes a vertical pipe 1, a change-direction curved pipe 2, a variable-section pipe 3, a casting device 4 and a movable baffle 5; the vertical pipe 1 and the change-direction curved pipe 2 form an L-shaped structure, the variable-section pipe 3 is connected to the outlet end of the vertical curved pipe 2, the variable-section pipe 3 is connected to the inlet of the casting device 4, and the movable baffle 5 is arranged at the outlet end of the casting device 4. Specific embodiment 2:

[0065] A low-carbon phase-change energy storage UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 360 parts of fly ash, 240 parts of silica fume, 440 parts of water, 1200 parts of machine-made sand, 1700 parts of phase-change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0066] The raw material modification method and the preparation method of the above-mentioned low-carbon phase change energy storage UHPC are the same as those in specific embodiment 1. Specific embodiment 3:

[0068] A low-carbon phase-change energy storage UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 320 parts of fly ash, 280 parts of silica fume, 480 parts of water, 1200 parts of machine-made sand, 1700 parts of phase-change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0069] The raw material modification method and the preparation method of the above-mentioned low-carbon phase change energy storage UHPC are the same as those in specific embodiment 1.

[0070] Comparative Example 1:

[0071] A UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 400 parts of fly ash, 200 parts of silica fume, 400 parts of water, 1200 parts of machine-made sand, 1700 parts of phase change aggregate, 2 parts of carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0072] In Comparative Example 1, the carbon fiber was not modified, and the remaining raw material modification methods and the above-mentioned method for preparing a UHPC were the same as those in Specific Example 1.

[0073] Comparative Example 2:

[0074] A UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 400 parts of fly ash, 200 parts of silica fume, 400 parts of water, 1200 parts of machine-made sand, 1700 parts of crushed stone, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

[0075] In Comparative Example 2, the phase change aggregate is replaced with crushed stone with the same particle size range and continuous grading, and the remaining raw material modification methods and the above-mentioned method for preparing a UHPC are the same as those in Specific Example 1.

[0076] Comparative Example 3:

[0077] A UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 400 parts of fly ash, 200 parts of silica fume, 400 parts of water, 1200 parts of machine-made sand, 1700 parts of phase change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, and 1 part of sodium polyacrylate.

[0078] In Comparative Example 3, no setting agent is added, and the modification method of other raw materials is the same as that of Specific Example 1.

[0079] The above-mentioned method for preparing a UHPC is as follows:

[0080] N1. Weighing materials: According to the test mix ratio, calculate the mixing amount of each material and accurately weigh the mass of each material.

[0081] N2. Concrete configuration:

[0082] N21. Mixed liquid preparation: Add polycarboxylic acid high-performance water reducer to 50% water and stir for 3 minutes to obtain aqueous solution α; add modified carbon fiber and sodium polyacrylate to the remaining 50% water and stir for 3 minutes to obtain aqueous solution β containing modified carbon fiber.

[0083] N22. Concrete mixing: Place cement, fly ash and silica fume in a dry mixer and stir for 2 minutes; stop the machine, add machine-made sand and stir for 1 minute; stop the machine, add the phase change aggregate with pre-wetted surface and stir for 1 minute; keep stirring, add aqueous solution α and stir for 1 minute, keep stirring, add aqueous solution β containing modified carbon fiber and stir for 3 minutes to make the mixture uniform.

[0084] N3. Concrete pouring, vibration and curing: Pour the concrete into the "L" deformed cross-section concrete pouring device, keep the concrete surface 1 / 3 away from the top surface of the pouring device, open the movable partition 5 at the pouring device outlet, and allow the concrete to flow outwards to the mold coated with a release agent under the action of gravity. Each time the concrete is poured to 1 / 4 of the height, place the test mold on the vibration table and vibrate to expel the internal bubbles to achieve a dense effect; after the concrete pouring and vibration are completed, scrape the film flat, and remove the mold after curing under natural conditions for 24 hours. After the demolding is completed, the test piece will be subjected to standard curing.

[0085] Comparative Example 4:

[0086] A UHPC is prepared from the following raw materials in parts by weight: 1400 parts of cement, 400 parts of fly ash, 200 parts of silica fume, 400 parts of water, 1200 parts of machine-made sand, 1700 parts of phase change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, and 1 part of sodium polyacrylate.

[0087] In Comparative Example 4, the concrete pouring does not take the fiber orientation into consideration, that is, the "L"-shaped variable-section concrete pouring device is not used for pouring. The remaining raw material modification methods and the above-mentioned UHPC preparation method are the same as those in Specific Example 1.

[0088] The mixed slurries in Specific Examples 1-3 and Comparative Examples 1-4 were poured into a mold to prepare test blocks.

[0089] Among them, the test blocks for testing compressive strength are cubic test blocks with dimensions of 100mm×100mm×100mm. After molding, they are cured in a standard curing room for 7d and 28d, and the concrete surface layer perpendicular to the fiber orientation is used as the compressive surface. The test method refers to GB / T 50081-2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete"; according to GB / T 50080-2016 "Standard Test Methods for Performance of Ordinary Concrete Mixtures", the slump of concrete is tested.

[0090] Among them, the test block for testing thermal conductivity is a cubic test block with a size of 300mm×300mm×300mm. After molding, it is cured in a standard curing room for 28 days. The test block is placed in an oven at a temperature of (60±5)℃ and dried to constant weight and then cooled to room temperature. The test method refers to GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of insulation materials - Guarded hot plate method"; the test method for structural heat storage coefficient refers to GB 50176 "Code for Thermal Design of Civil Buildings", in which the thermal conductivity and heat storage coefficient tests should use the concrete surface layer parallel to the fiber orientation as the test surface.

[0091] The test results of basic concrete properties are as follows:

[0092] Table 1 Test results of basic properties of concrete

[0093]

[0094]

[0095] It can be seen from the table that the UHPC prepared in the specific examples 1-3 and comparative examples 1-4 of the present invention has excellent mechanical properties and workability, can meet the increasingly high requirements for the mechanical properties of UHPC in the construction field, and has a large market prospect.

[0096] From the comparison of specific embodiments 1-3, it can be seen that with the increase of water-cement ratio, the 7d and 28d strengths of low-carbon phase change energy storage UHPC gradually decrease, and there is no strength shrinkage, which is in line with the development trend of the relationship between UHPC strength and water-cement ratio, indicating that the strength development of concrete is good within this water-cement ratio range.

[0097] From the comparison between comparative example 1 and specific example 1, it can be seen that the 7d and 28d compressive strength of the concrete without strength enhancement modification of the carbon fiber is reduced, and the 7d and 28d strengths are reduced by 8.11% and 7.08% respectively compared with specific example 1. From the comparison between specific example 1 and comparative example 3, it can be seen that the strength of the concrete without the addition of the setting regulator is significantly reduced, and the 7d and 28d strengths are reduced by 8.11% and 7.08% and 12.94% and 18.40% respectively compared with specific example 1. It shows that reasonable raw material modification is beneficial to the growth of the strength of low-carbon phase change energy storage UHPC.

[0098] The test results of concrete heat storage and release capacity are as follows:

[0099] Table 2 Test results of concrete heat storage and release capacity

[0100]

[0101] It can be seen from the table that the UHPC prepared in specific embodiments 1-3 of the present invention has excellent thermal conductivity and heat storage capacity.

[0102] By comparing Comparative Example 2 with Specific Example 1 and combining with Table 1, it can be seen that although the strength of UHPC is significantly reduced after adding phase change aggregate, its thermal conductivity and heat storage capacity are increased, which can better meet the functional requirements of UHPC.

[0103] By comparing Comparative Example 4 with Specific Example 1 and combining with Table 1, it can be seen that the strength of carbon phase change energy storage UHPC increases well after considering fiber orientation, and the 7d and 28d compressive strengths increase by 8.61% and 32.34% respectively, and the thermal conductivity and heat storage capacity of UHPC increase. The possible reasons are as follows: (1) Considering the obvious increase in the thermal conductivity of phase change energy storage UHPC after fiber orientation, the PCM heat storage capacity is fully utilized, and the heating rate of UHPC is slowed down during coagulation and hardening, which reduces the maximum compressive stress of concrete and prolongs the second zero stress temperature time of UHPC, increasing the stress reserve of concrete. (2) The carbon fiber distribution in low-carbon phase change energy storage UHPC is more uniform, which can better resist the temperature stress of concrete.

[0104] Compared with related technologies, the low-carbon phase change energy storage UHPC of the present invention has the following advantages:

[0105] 1. Adding PCM to UHPC enables concrete to store and release heat, which can provide thermal insulation, regulate indoor temperature, and reduce resource and energy consumption. At the same time, concrete also has high strength and can appropriately reduce the size of structural components according to design requirements. It can be applied to the main structural components and enclosure structures to increase the structural clearance, expand the usable area of ​​the building structure, and make the arrangement of structural components more flexible.

[0106] 2. Adopt a multi-dimensional crack control method: Add modified reinforced carbon fiber to increase the tensile strength of concrete, resist early temperature stress, and thus reduce the impact of temperature shrinkage on concrete; add PCM to utilize its heat storage and release capacity to reduce its heating rate, reduce early temperature stress, and prevent the structure from producing through cracks and deep cracks; pour concrete in layers, and add setting agents to the upper concrete to reduce its setting rate to form a "flexible support", reduce the temperature stress between concrete layers, and ensure construction quality; use phase change aggregate pre-absorption to ensure the internal humidity of concrete to reduce the impact of its self-shrinkage on concrete structural components.

[0107] 3. Considering fiber dispersion and fiber orientation, the mechanical properties of concrete are improved while ensuring its thermal conductivity efficiency, so that the heat storage and release capacity of PCM can be fully utilized and the temperature control ability of concrete components can be improved.

[0108] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A low-carbon phase change energy storage UHPC, characterized in that: Its components and weight proportions are: 1400 parts of cement, 320-400 parts of fly ash, 200-280 parts of silica fume, 400-480 parts of water, 1200 parts of machine-made sand, 1700 parts of phase change aggregate, 2 parts of modified carbon fiber, 20 parts of polycarboxylic acid high-performance water reducing agent, 2 parts of composite setting regulator, and 1 part of sodium polyacrylate.

2. A low-carbon phase change energy storage UHPC according to claim 1, characterized in that: The preparation method of phase change aggregate is as follows: S1. Granite surface modification: high temperature burning of granite for surface modification; S2. Vacuum adsorption of phase change material: using n-dodecane as phase change material, placing a beaker containing liquid phase change material and modified granite in a glass kettle and starting the vacuum pump for 30-40 minutes. When the modified granite immersed in the liquid phase change material no longer emits bubbles, the pores in the modified granite are completely filled with the phase change material. S3. Post-processing of phase change aggregate: stop vacuuming, slowly turn the air inlet valve to restore the pressure in the glass kettle to normal pressure, take out the modified granite that has absorbed the phase change material and put it into a refrigerator at 4°C, and carry out subsequent packaging work after the phase change material in the modified granite becomes solid. The cement slurry is modified with 30% by mass epoxy resin and evenly wrapped on the outer surface of the phase change granite. The wrapping thickness is controlled to be 0.5-1.0mm, and the modified cement slurry is solidified to obtain the phase change aggregate.

3. A low-carbon phase change energy storage UHPC according to claim 2, characterized in that: The particle size of phase change aggregate is 8-11mm.

4. A low-carbon phase change energy storage UHPC according to claim 3, characterized in that: The modification method of modified carbon fiber is as follows: P1. Preparation of carboxylated carbon fiber: Weigh 5 parts of carbon fiber, the carbon fiber used is T700-12K carbon fiber, the length is 10 mm, pour it into a beaker filled with a mixed solution of 98% concentrated sulfuric acid and 70% concentrated nitric acid in a volume ratio of 3:1, stir evenly, put it into a magnetic stirring rotor and coat it, move the beaker to a magnetic heating stirrer, stir it at 300 rad / min for 6 hours under the condition of heating in a water bath at 60°C, take out the beaker and let it stand to room temperature, then dilute the mixed solution in the beaker, filter it with a vacuum filter, wash the oxidized carbon fiber to neutrality, put it in a vacuum oven, and dry it at 65°C for 24 hours to obtain carboxylated carbon fiber; P2. Preparation of multi-walled carbon nanotube dispersion: Weigh 1 portion of carbon nanotubes, pour into a beaker containing 50 ml of dimethylformamide, add TNDWIS aqueous dispersant dropwise at a mass ratio of 1:5, stir magnetically for 15 minutes and then coat, move the coated beaker into an ultrasonic cell crusher, and ultrasonicate at 30% power for 30 minutes to obtain a multi-walled carbon nanotube dispersion; P3. Modification of carbon fiber grafted with multi-walled carbon nanotubes: Add the carboxylated carbon fiber obtained in step P1 to the beaker containing the multi-walled carbon nanotube dispersion obtained in P2, then add a few drops of concentrated sulfuric acid, transfer to a constant temperature magnetic stirrer, heat in a 60°C water bath at 50% power, and turn on the ultrasonic equipment and magnetic stirring equipment at the same time, so that the mixed liquid is stirred while being ultrasonically treated, and the stirring speed is 450 rad / min, and the stirring is carried out for 2 hours. After the stirring is completed, remove the beaker from the device and let it stand to room temperature, and then use a vacuum filter to wash the reaction product several times, and finally put it into a vacuum drying oven and dry it at 65°C for 24 hours to obtain modified carbon fiber.

5. A low-carbon phase change energy storage UHPC according to claim 4, characterized in that: The cement is P·Ⅱ52.5 silicate cement.

6. A low-carbon phase change energy storage UHPC according to claim 5, characterized in that: The average particle size of machine-made sand is 130μm, the maximum particle size is 250μm, and the gradation is continuous.

7. A low-carbon phase change energy storage UHPC according to claim 6, characterized in that: The composite coagulant is prepared by compounding 0.2% sodium citrate and 1% sodium gluconate.

8. The method for preparing a low-carbon phase change energy storage UHPC according to claim 7, characterized in that: The specific steps are as follows: Y1. Weighing materials: According to the test mix ratio, calculate the mixing amount of each material, accurately weigh the mass of each material and divide it into two equal parts according to mass to prepare concrete ① and concrete ②; Y2. Concrete① configuration: Y21, mixed solution ① configuration: add polycarboxylic acid high-performance water reducing agent and composite setting agent to 50% water and stir for 3 minutes to obtain aqueous solution α; add modified carbon fiber and sodium polyacrylate to the remaining 50% water and stir for 3 minutes to obtain aqueous solution β containing modified carbon fiber; Y22. Concrete ① Mixing: Place cement, fly ash and silica fume in a dry mixer and mix for 2 minutes; stop the mixer and add machine-made sand and mix for 1 minute; stop the mixer and add the phase change aggregate with pre-wetted surface and mix for 1 minute; keep stirring and add aqueous solution α and mix for 1 minute; keep stirring and add aqueous solution β containing modified carbon fiber and mix for 3 minutes to make the mixture evenly stirred; Y3. Concrete② configuration: Y31, mixed solution ② configuration: the aqueous solution γ does not contain a composite coagulant, and the rest of the configuration method is the same as the aqueous solution α; the aqueous solution ξ containing modified carbon fiber is configured in the same way as the aqueous solution β containing modified carbon fiber; Y32. Concrete② Mixing: Place cement, fly ash and silica fume in a dry mixer and mix for 2 minutes; stop the mixer and add machine-made sand and mix for 1 minute; stop the mixer and add the phase change aggregate with pre-wetted surface and mix for 1 minute; keep stirring and add the aqueous solution γ and mix for 1 minute; keep stirring and add the aqueous solution containing modified carbon fiber ξ and mix for 3 minutes to make the mixture evenly stirred; Y4. Concrete pouring, vibration and maintenance: Concrete ① and concrete ② are poured into their respective "L" deformed cross-section concrete pouring devices, and the concrete surface is kept 1 / 3 away from the top surface of the pouring device. The movable baffle plate (5) at the pouring device outlet containing concrete ① is opened to allow concrete ① to flow outwards into the mold coated with a release agent under the action of gravity. Each time the concrete is poured to 1 / 4 of the height, the test mold is placed on a vibrating table to expel internal bubbles through vibration to achieve a compacting effect, until the concrete is poured to 1 / 2 of the height of the test mold; the movable baffle plate (5) at the pouring device outlet containing concrete ② is opened to allow concrete ② to flow outwards into the mold under the action of gravity. Each time the concrete is poured to 1 / 4 of the height, the test mold is placed on a vibrating table to expel internal bubbles through vibration to achieve a compacting effect; after the concrete pouring and vibration are completed, the film is scraped flat, and the mold is removed after curing for 24 hours under natural conditions. After the demolding is completed, the test piece is subjected to standard curing.

9. The method for preparing a low-carbon phase change energy storage UHPC according to claim 8, characterized in that: In step Y4, the "L"-shaped variable-section concrete pouring device comprises a vertical pipe (1), a direction-changing curved pipe (2), a variable-section pipe (3), a pouring device (4) and a movable baffle (5); the vertical pipe (1) and the direction-changing curved pipe (2) form an L-shaped structure, the variable-section pipe (3) is connected to the outlet end of the vertical curved pipe (2), the variable-section pipe (3) is connected to the inlet of the pouring device (4), and the movable baffle (5) is arranged at the outlet end of the pouring device (4).

Citation Information

Cited By

  • High-ground-temperature-resistant ultra-high-performance concrete as well as preparation method and application thereof

    CN120004566A

  • An ultra-high performance concrete resistant to high ground temperature, its preparation method and application

    CN120004566B

  • Phase change energy storage type low-carbon ultra-high performance concrete and preparation method thereof

    CN120698743A